Social Factors Associated with Mental Health Status Among Undergraduate Students of Medical Science in Nepal - Joshi, Naresh Prasad; Bhandari, Roshan; Joshi, Ganga Prasad; Joshi, Dinesh Raj; Kalauni, Bhoj Raj; Joshi, Dhaneshwari; Paudyal, Richa (A Bi-annual South Asian Journal of Research & Innovation, 2024)
Medical education is inherently demanding, often impacting the mental well-being of students. This study investigates the social factors associated with mental health status—specifically depression, anxiety, and stress—among undergraduate students of medical sciences in Nepal. To explore how sociological determinants such as academic pressure, social support networks, socioeconomic background, and interpersonal interactions influence mental health outcomes in students at Maharajgunj Medical Campus, Kathmandu. A quantitative cross-sectional study was conducted among 210 undergraduate MBBS students, selected through simple random sampling from a total population of 429 students. Data were collected via a semi-structured, self-administered questionnaire disseminated through Google Forms. Mental health status was assessed using the globally validated DASS-21 scale, while socio-demographic and academic data were also gathered. Findings revealed that academic stress is a primary contributor to increased levels of anxiety and depression, consistent with Structural Functionalist interpretations of institutional pressures. Students lacking robust social support networks reported higher stress levels, emphasizing the relevance of Social Support Theory. Moreover, Conflict Theory helps explain the disproportionate mental health burden among students from lower socioeconomic backgrounds, particularly those from rural areas, who face challenges adjusting to urban academic settings. Symbolic Interactionism highlights how perceived stigma, and negative social interactions further deteriorate mental well-being. Sociological determinants play a significant role in shaping the mental health status of medical students. Interventions should prioritize strengthening peer and institutional support systems, addressing academic workload management, and combating mental health stigma on campus. Special attention is warranted for students from rural and underprivileged backgrounds, as well as female students, through targeted mental health services and inclusive academic policies. This study underscores the importance of a multidimensional approach that integrates sociological understanding to promote mental wellness in medical education settings.